Do older people with visual impairment and living alone in a rural developing country report greater difficulty in managing stairs? - Hairi, N.N.; Bulgiba, A.; Peramalah, D.; Mudla, I. (2012)
Objectives: Managing stairs is a challenging activity of daily living (ADL) for older people. This study aims to examine the association between visual impairment and difficulty in managing stairs among older people living alone and those living with others. Methods: A population-based cross sectional study was conducted in rural Malaysia from 2007 till 2008. Seven hundred and sixty five older people aged 60 years and over underwent eye examination for visual impairment. Visual acuity criteria were used to define visual impairment. Presenting visual acuity was assessed using a standard metric Snellen Chart of E type. Difficulty in managing stairs was measured according to a question drawn from the Barthel Index which asks âdo you need help in climbing stairsâ. Results: Overall, the prevalence of difficulty in managing stairs among older people in our population was 135 (18.3, 95 CI 15.7â21.2). After adjusting for important confounders the odds ratio (OR) for visual impairment and difficulty in managing stairs among older people living alone was 5.04 (95 CI 2.27, 10.62). Among older people living with others, the adjusted OR for visual impairment and difficulty in managing stairs was 3.10 (95 CI 1.52, 6.80). Conclusion: In a sample of older people aged 60 years and over, those living alone with visual impairment had greater difficulty in managing stairs than those living with others. Identification of these groups of older people is useful for targeting interventions.